C.2 - Douglas Mary. (London, 1980)
The books contains following topics: Introduction; Human Mental Faculties; The Continuity of Evans-Pritchard's Programme ; Fieldwork Methods; Accountability among the Nuer; Accountability among the Azande; Reasoning and memory.
Keywords: Evans Prichard